2014
DOI: 10.1523/jneurosci.2060-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Munc13-3 Superprimes Synaptic Vesicles at Granule Cell-to-Basket Cell Synapses in the Mouse Cerebellum

Abstract: Munc13-3 is a presynaptic protein implicated in vesicle priming that is strongly expressed in cerebellar granule cells (GCs. Neither presynaptic Ca 2ϩ influx was affected by deletion of Munc13-3 nor replenishment of the readily releasable vesicle pool. However, a high concentration of EGTA led to a reduction in EPSCs that was significantly stronger in Munc13-3 Ϫ/Ϫ . We conclude that Munc13-3 is responsible for an additional step of molecular and/or positional "superpriming" that substantially increases the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 51 publications
11
37
0
Order By: Relevance
“…Munc13-3 is strongly expressed in PF varicosities (PF v s). Notably, its expression is upregulated during development (Augustin et al, 1999), and Munc13-3-deficient synapses have decreased p r (Augustin et al, 2001;Ishiyama et al, 2014). These findings would be consistent with a role of Munc13-3 in regulating AZ topography and coupling distances during development.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Munc13-3 is strongly expressed in PF varicosities (PF v s). Notably, its expression is upregulated during development (Augustin et al, 1999), and Munc13-3-deficient synapses have decreased p r (Augustin et al, 2001;Ishiyama et al, 2014). These findings would be consistent with a role of Munc13-3 in regulating AZ topography and coupling distances during development.…”
Section: Introductionsupporting
confidence: 75%
“…than in tight coupling regimes (Adler et al, 1991). Previously, we found that loading of PF v with membrane-permeable EGTA (EGTA-AM) significantly affects release from young (postnatal day [P] 8-10) but not from matured (P21-P24) PF terminals onto PNs in the WT (Baur et al, 2015) and that EGTA-AM affects release at mature PF to basket cell (BC) synapses in Munc13-3 À/À but not in WT mice (Ishiyama et al, 2014). These data would be compatible with a critical role of Munc13-3 in the maturation of the release process.…”
Section: Impaired Developmental Tightening Of Coupling In Munc13-3 à/àmentioning
confidence: 99%
“…Furthermore, at parallel fibre to Purkinje cell synapses, Munc13‐3 mediates super‐priming (Ishiyama et al . ), most probably by shortening the coupling distance (Kusch et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Using styryl dyes and cultured hippocampal neurons, strong heterogeneity of release was observed among individual boutons, when stimulating at 1 Hz, whereas synaptic strength was more uniform, with some of the remaining heterogeneity disappearing after a few stimuli, when stimulating at 10 Hz (47). Ishiyama et al (65) describe a decrease in p in granule cell to basket cell synapses of the cerebellum of Munc13-3 −/− mice. They interpret their observations as a loss of a superpriming action of Munc13-3.…”
Section: Superpriming May Be a Widely Spread Phenomenon Among Excitatorymentioning
confidence: 99%